Controlled release system for delivery of GET peptide and its application for transcription factor delivery for bone regeneration - Abu Awwad, Hosam Al-Deen (2018)
The repair of bone defects and non-union fractures is a significant challenge for clinicians as it requires tissue replacement. The current graft approaches used to treat these injuries have limitations with regard to quality and availability. This has resulted in research efforts to develop alternative synthetic materials that are able to aid tissue regeneration. These materials usually combined with biological factors to induce cells proliferation and differentiation. Transcription factors can provide specific regulatory effect, however, these transcription factors are very difficult to be delivered intracellularly. A recent work, conducted at Tissue Engineering group – University of Nottingham, has shown that recombinant transcription factors can be expressed, purified and delivered efficiently to control cell behaviour for further tissue engineering applications. Efficient delivery of these factors can be achieved by using Glycosaminoglycan-binding enhanced transduction (GET) peptides, which are multi-domain peptides comprising a GAG-binding peptide (to promote cell interaction) and a cell-penetrating peptide (CPP) for high efficiency membrane transduction. The aim of the work presented in this thesis was to develop a poly-(lactic-co-glycolic acid) (PLGA) based delivery system to release RUNX2 transcription factor, which is significantly involved in osteogenesis. GET peptide was utilised to enhance the intracellular delivery of RUNX2. The advantage of this system is to control the dose and localisation of the released RUNX2 as well as providing a biodegradable scaffold to support the newly formed tissue. Reproducible procedures were developed to manufacture spherical PLGA microparticles (MPs) using Solid-in-oil-in-water (S/O/W) emulsion method. Red florescent protein (RFP) coupled with GET peptide was used as model protein to evaluate the stability of peptide during microparticles fabrication and release. Efficient encapsulation (~65%) and tailored protein release profiles could be achieved, however intracellular transduction was significantly inhibited post-release. Co-encapsulation of L-Histidine, which may form a complex with the PLGA degradation products under acidic conditions, was used as a strategy to retain GET peptide activity. Simulations of the polymer microclimate showed that hydrolytic acidic PLGA degradation products directly inhibited GET peptide transduction activity, use of L-Histidine significantly enhanced released protein delivery. GET-RUNX2 was efficiently encapsulated (~60%) within PLGA MPs using the developed S/O/W method and release profile was adopted to match the optimal RUNX2 dose needed to induce osteogenesis of hMSCs (i.e. 60μg in the first 7 days of the study). GET-RUNX2 activity post release was evaluated. Results showed comparable transduction and transfection activities (compared to experimental control) throughout the release period. GET-RUNX2 loaded MPs were mixed with temperature-sensitive PLGA/PEG particles to provide scaffold structures. hMSCs were used for an in-vitro differentiation assessments. Osteogenesis gene markers were comparable to experimental controls for both early and late markers. Moreover, the scaffold formula was optimised to be 3D printable to provide complex and irregular shape scaffolds matching defect size. The ability to control intracellular transduction of functional proteins into cells will facilitate localised delivery of therapeutics, with minimised risk of systemic dosing that may lead to non-targeted activity, and allow approaches to direct cellular behaviour for regenerative medicine applications.